Strategi Pengembangan Desa Wisata Oleh Pemerintah Desa Perspektif Etika Bisnis Islam (Studi Kasus Desa Pulau Miang Kecamatan Sangkulirang) - Dyanul Khatimah; Satriah; Hasan (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study examines the development strategy of Miang Island Tourism Village through the perspective of Islamic business ethics, amidst the challenges of limited infrastructure and human resources. With a qualitative case study approach, data were collected from in-depth interviews and official documents. The results of the study indicate that there is collaboration between the village government, Pokdarwis, and local communities in developing tourism villages. The strategic steps taken include Pokdarwis training, construction of piers and public facilities, and tourism promotion through social media @MiangIsland. This strategy also reflects the principles of Islamic business ethics, such as mangrove conservation and community economic empowerment through homestay businesses and souvenir sales.